AI Integration in Islamic Religious Education Learning in Madrasahs: Impact Analysis on Digital Literacy and the Formation of Students' Spiritual Character - Ita Yunita; Abdulloh Hamid; Syaifuddin Syaifuddin (Intiqad: Jurnal Agama dan Pendidikan Islam, 2026)
This study aims to examine the practice of AI integration in PAI learning and analyze its influence on digital literacy and the formation of students' spiritual character. Using a qualitative approach with a case study design. Data was obtained through interviews, observations, and documentation analysis of teachers, students, and madrasas. The results show that the use of AI has a positive impact on improving students' digital literacy, especially in the ability to access, understand, and utilize technology critically, ethically, and responsibly. AI-based learning media also increases motivation and learning participation through the presentation of adaptive and interactive materials. However, ethical and spiritual problems were found, such as a decline in the emotional closeness of student teachers and the potential for weakening of manners and religious awareness. Therefore, an integrative approach is needed that combines intelligent technology with the internalization of moral values so that AI functions as a support for character formation in Islamic education. This research contributes to the development of an AI-based PAI learning model that emphasizes digitalization as well as transcendental values.